Studi Efektivitas Ekstrak Daun Sereh Wangi (Cymbopogon nardus L.) Sebagai Anti Fungi Candida albicans - Eka Fitriani; Muhammad Alwi; Umrah Umrah (Biology Department, Mathematics and natural science, Tadulako University, 2013)
The study was held on effectiveness of extract lemongrass leaf (Cymbopogon nardus L.) as a anti septic of Candida albicans. The study conducted as long as 3 months, from march to may 2013. Extracts was obtained by maceration method. This study aims to determine the extract can be prevent the growing of the Candida albicans, and to determine the effective concentration to prevent the growing of the fungus Candida albicans. This study is an experimental research with a completely randomized design. Bes trew diffusion method by a concentration of 25%, 50%, 75%, 100% and metronidazol liquid is used to determine the zone diameter inhibition in the five treatment and five replications. Inhibition zone diameter data were analyzed statistically ANOVA and Duncen Multiple Range Test (DMRT). The concentration stratified of extract effect on the zone diameter growth of Candida albicans. Based on the study, concentration at 75% is the best to be inhibited the growth of Candida albicans in conclusion, the extract is anti septic to the growth of Candida albicans. Keywords: Cymbopogon nardus L., Maceration, Candida albicans